Current Ratio (CR), Debt to Asset Ratio (DAR) Dan Total Assets Turnover (TATO) Terhadap Return On Asset (ROA) - Goenawan Soedarso, Herry; Dewi, Lusiana (CV. Lafadz Jaya, 2022)
This study aims to empirically prove the Current Ratio (CR), Debt To Asset Ratio (DAR) and Total Assets Turnover (TATO) to Return On Assets (ROA). In this study there are 3 independent variables tested Current Ratio (CR), Debt To Asset Ratio (DAR) and Total Assets Turnover (TATO). The population of this study is food and beverage companies in 2018-2020. The sampling technique used is purposive sampling, so as to obtain a sample of 12 companies. This research was conducted in 2018-2020, so the amount of data in this study was 36 data. The analytical method used is multiple linear regression with SPSS V.20. The results of the study prove that Accounts Receivable Turnover affects the profitability of food and beverage companies listed on the Indonesia Stock Exchange in 2018-2020. Current ratio and Debt To Asset Ratio affect the return on assets of food and beverage industry companies listed on the Indonesia Stock Exchange. Total Assets Turnover has no effect on return on assets in food and beverage industry companies listed on the Indonesia Stock Exchange.